Páginas da vida de um jovem arqueólogo: Francisco Tavares Proença Júnior (1883-1916) - Ana Cristina Martins (Midas: Museus e Estudos Interdisciplinares)
Inaugurated in 1910, the Municipal Museum of Castelo Branco was born from the will and action of Francisco Tavares Proença Júnior (1883-1916), then 27 years old. Belonging to one of the most influential families of the time, F. Tavares Proença Júnior soon became interested in the past of the region where he lived, going through it in search of archaeological sites he pointed out and artefacts that he collected in order to constitute a collection that would be at the base of the museum that he planned to institute since 1902, regardless of multiple discouragements and contradictions. It was, however, an individual plan of public visibility that deserves to be analyzed as a materialization of an agenda of personal affirmation based on fundings provided by his family. We propose, therefore, to demonstrate, in this article, the relationship maintained between the personality F. Tavares Proença Júnior, his incomes, territory, collection, museum and identity(s).